Analisis Kinerja Web Disdukcapil Dengan Menggunakan Heuristic Evaluation Dan Webuse Web Performance Analysis with Heuristic Evaluation and Webuse - Listiya, Resy (Puslitbang Akademi Relawan TIK Indonesia, 2024)
The Disdukcapil website of South Lampung Regency is a service access to a website that has moved to serve the community for every complaint of the community and information that can be accessed online. Since this website has been operating, there has never been a change or evaluation. This study uses web-based methods and heuristic evaluation. Webuse can calculate the user's individual satisfaction and assessment of websites using structured and accurate tools, while the calculation of heuristic evaluation aims to determine guidelines, general principles, and/or regulations that can guide design decisions and/or be used in evaluation and provide criticism and suggestions on decisions that are made. This research was conducted by spreading questions to 50 respondents. The results of the Heuristic Evaluation of Webuse (Heuristic Evaluation) on the Disdukcapil website in South Lampung Regency have met usability requirements efficiently and effectively and provide freedom to users in using the Disdukcapil website in South Lampung Regency. The evaluation results that have been carried out on the recommendations are adrift with the